ANALISIS TINGKAT KEPUASAN KONSUMEN TERHADAP PELAYANAN USAHA BENIH PADI CIGEULIS - Patimah, Siti; Priyono, Basuki Sigit; Rasyid, Witman (Jurnal AGRISEP, 2016)
This research was conducted in Kepahiang District, Bengkulu Province which had been held from April 29, 2015 until May 29, 2015. The purposes of this study were (1). To determine level of service quality rice seed Cigeulis in BBIPP, (2). To determine level of Satisfaction of consumers to services rice seed Cigeulis. The method used for the service is a method Importance Performance Analysis (IPA) and the level of satisfaction using the Customer Satisfaction Index (CSI). From the CSI service Cigeulis rice seed in the district Kepahiang Bengkulu province amounted to 80,35% of this index is on a scale satisfied.